Financial Literacy among Students of Nilkantha Multiple Campus - Rupakheti, Ram Chandra (Research Nepal Journal of Development Studies, 2020)
The purpose of this research is to assess the level of financial literacy and its impact on college students in Nepal. This study surveys 60 students from Nilakantha Multiple Campus out of 896 students. This research used a structured questionnaire complemented by multiple choices to select the correct answer. The students taken for the study were from BBS group. Each 60 students have filled the questionnaire. The research reveals that financial literacy among students appears to be below the average level. It can be concluded that students have poor financial planning. Students have not enough knowledge about the importance of savings. Budgeting and financial plan of students have been found below average level. The overall students’ performance in the questions found 49.84% which is below the benchmark of Chen, Volpe, and Pavlicko. Overall, the study reveals that students were not as financially literate as expected. It is, therefore, recommended that a comprehensive and aggressive program of financial education be carried out especially among young people in Nepal by policy makers.